Nasal colonization in children with community acquired methicillin-resistant Staphylococcus aureus - Fazlollah Davoodabadi (Advanced Biomedical Research, 2016)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a frequent cause of infections. The changing epidemiology of MRSA became evident in the 1990s when CA-MRSA cases were first reported. Nasal carriage of CA-MRSA is associated with an increased risk for development of infections in various populations. Materials and Methods: Anterior nares culture for the presence of methicillin-susceptible Staphylococcus aureus (MSSA) and MRSA was taken from 345 children attending kindergartens, who didn't have any known risk factor for MRSA colonization. Also, children demographic variables were recorded. Identification of SA and community-acquired methicillin-resistant Staphylococcus aureus ( CA-MRSA) with standard microbiological test was performed. Finally, the susceptibility of isolated to various antibiotics determined. The data were analyzed with Whonet 5.6 software. Results: Of 345 children, 20 children (5.8%) were colonized with CA-MRSA, 86 children (24.9%) with MSSA and 239 cases (69.3%) didn't have SA colonization. The highest rate of MSSA and MRSA colonization was obtained at the age of 6 years. The frequency distribution of SA (MSSA and MRSA) colonization prevalence didn't have any significant differences based on age, gender and the admission time (P > 0.05); but it was significantly different in the urban areas (P < 0.001). The lowest resistance rate of CA-MRSA isolates, with a frequency of 10%, was detected with gentamicin, rifampin, and trimethoprim-sulfamethoxazole. Conclusions: In summary, CA-MRSA colonization was observed in child care centers remarkably. Therefore, by facing various infections due to SA especially in areas of low socio-economic status, it must be considered. Based on antibiogram test, empirical treatment with rifampin, gentamicin and ciprofloxacin is recommended during CA-MRSA infections.